Pengembangan Bahan Ajar Materi Trigonometri dengan Model Problem-Based Learning Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik SMA - Noptianus, Andrian; Ihsan, Iden Rainal (IAPM UNSUR (Ikatan Alumni Pendidikan Matematika Universitas Suryakancana))
The background of this research is the low ability of students in mathematical problem solving and not appropriate teaching materials yet to increase that skill. The first purpose is to compose and developed teaching matherial with valid and practical process. The second purpose is to know the increasing of students ability in the mathematical problem solving in use developed teaching materials. The third purpose is to know the students responses of students about developed teaching materials. The research methodology was R&D and quasi experimental, with design model of Tessmer. The Subjects is all students of class X MIPA, teacher of mathematics in a one of public senior high school in Bandung, and lecturer of mathematics education. Data was collected though validation, limited testing, and field test of teaching materials. Based on the result of data processing and analysis in development of teaching materials has three conclusions. The first, teaching materials that compose and developed are valid, practical, and accordance with national curriculum. The presentment of developed teaching material is in accordance with the model problem-based learning. The second, developed teaching material increasing students ability in mathematical problem solving. The third, the students give a positive responses to developed teaching materials.